ISLAMIC ACCOUNTING RESEARCH DEVELOPMENT WITH SCOPUS DATABASE ANALYSIS VISION VIEWER - Rustandi, Nanang; Fitriana, Fitriana; Santoso, Rahmat Agus (El-Ecosy : Jurnal Ekonomi dan Keuangan Islam, 2025)
Penelitian dalam bidang Islamic Accounting masih sedikit dan terbatas. Tujuan penelitian untuk mengetahui tren publikasi, jaringan kolaborasi peneliti, kluster perkembangan publikasi, serta pemetaan konsep utama literatur Islamic Accounting. Metode pengumpulan data melalui penelusuran data publikasi terindeks scopus pada aplikasi Publish lewat kata kunci Islamic Accounting dengan kata kunci judul tahun 2003-2024. Hasil penelitian menggunakan Bibliometrik sofware VOSviewer 1.6.20. Hasil penelitian menunjukkan perkembangan jumlah publikasi terkait Islamic Accounting mencapai 135 jurnal terindeks Scopus dan menemukan 358 items dan 33 cluster, penelitian yang merujuk pada topik Islamic Accounting tertinggi terjadi pada tahun 2023 mencapai 23 publikasi (17.04%) dan Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) menempati cluster pertama dengan 26 items yang membahas accounting and auditing, accounting pinciples and banking, sehingga penelitian Islamic Accounting bisa mengidentifikasi peluang penelitian di masa depan. Research in the field of Islamic Accounting is still limited. The purpose of this study was to investigate publication trends, researcher collaboration networks, and publication development clusters, as well as to map the key concepts in Islamic Accounting literature. The data collection method involved searching Scopus-indexed publication data in the Publish application using the keyword "Islamic Accounting" and title keywords for the years 2003-2024. The research used bibliometric software VOSviewer 1.6.20. The results showed a growth in the number of publications related to Islamic Accounting, reaching 135 Scopus-indexed journals, which identified 358 items and 33 clusters. The highest number of research papers referring to Islamic Accounting topics occurred in 2023, reaching 23 publications (17.04%). The Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) occupied the first cluster with 26 items discussing accounting and auditing, accounting principles, and banking. This allows Islamic Accounting research to identify future research opportunities.